Detecting animal by-product intake using stable isotope ratio mass spectrometry (IRMS) - da Silva, D. A.F. [UNESP]; Biscola, N. P. [UNESP]; dos Santos, L. D. [UNESP]; Sartori, M. M.P. [UNESP]; Denadai, J. C. [UNESP]; da Silva, E. T. [UNESP]; Ducatti, C. [UNESP]; Bicudo, S. D. [UNESP]; Barraviera, B. [UNESP]; Ferreira, R. S. [UNESP] (Elsevier, 2016)
Sheep are used in many countries as food and for manufacturing bioproducts. However, when these animals consume animal by-products (ABP), which is widely prohibited, there is a risk of transmitting scrapie – a fatal prion disease in human beings. Therefore, it is essential to develop sensitive methods to detect previous ABP intake to select safe animals for producing biopharmaceuticals. We used stable isotope ratio mass spectrometry (IRMS) for 13C and 15N to trace animal proteins in the serum of three groups of sheep: 1 – received only vegetable protein (VP) for 89 days; 2 – received animal and vegetable protein (AVP); and 3 – received animal and vegetable protein with animal protein subsequently removed (AVPR). Groups 2 and 3 received diets with 30% bovine meat and bone meal (MBM) added to a vegetable diet (from days 16–89 in the AVP group and until day 49 in the AVPR group, when MBM was removed). The AVPR group showed 15N equilibrium 5 days after MBM removal (54th day). Conversely, 15N equilibrium in the AVP group occurred 22 days later (76th day). The half-life differed between these groups by 3.55 days. In the AVPR group, 15N elimination required 53 days, which was similar to this isotope's incorporation time. Turnover was determined based on natural 15N signatures. IRMS followed by turnover calculations was used to evaluate the time period for the incorporation and elimination of animal protein in sheep serum. The δ13C and δ15N values were used to track animal protein in the diet. This method is biologically and economically relevant for the veterinary field because it can track protein over time or make a point assessment of animal feed with high sensitivity and resolution, providing a low-cost analysis coupled with fast detection. Isotopic profiles could be measured throughout the experimental period, demonstrating the potential to use the method for traceability and certification assessments.
Keywords: Animal by-product intake; Sheep; Stable isotopes; δ13C value; δ15N value